Atomization behavior of composite liquid fuels based on typical coal processing wastes; Fuel Processing Technology; Vol. 225 - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Valiullin T. R. Timur Radisovich; Volkov R. S. Roman Sergeevich (2022, 2022)
Title screen